A process oriented approach to promoting collaborative practice: Incorporating complexity methods. (September 2014) - Solomon, P.; Risdon, C.
Abstract Background: Only recently have complexity informed methods been viewed as a strategy for changing health care systems and care delivery. Aims: This article reports on participants' perceptions of being involved in a complexity informed educational approach to promote interprofessional collaboration in a system of care for children with disabilities. Methods: Over a one-year period, all employees within a network of eight community agencies participated in three day-long workshops. A subset of twenty-four employees participated in eight monthly facilitated discussion groups. The workshops and discussion groups focused on processes rooted in complexity sciences which value small-scale interaction to improve the quality of discovery and shared problem solving. Learning group members (n = 24) and their facilitators (n = 4) participated in interviews and focus groups at the end of the project. Results: Qualitative content analyses of the transcriptions of the interviews and focus groups revealed that participants identified tangible benefits of the process oriented approach. Challenges related to the lack of structure and emergent nature of the methods were identified. Conclusions: Lessons learned include incorporating a gradual shift to emergent methods, fostering ownership from the beginning of the process, providing ongoing training to facilitators, flexibility and use of small-group scenarios.